Mediação de conflito socioambiental referente: uma análise da experiência da prefeitura municipal de Guarujá-SP, Brasil - Teixeira, Aníria Jose da Fonseca (2023)
Urban growth has been accompanied by significant changes in land use, leading to socio-environmental conflicts. In Brazil, the lack of tradition in mediation and socio-environmental conflicts is evidenced through numerous legal actions that often take years to reach a resolution. This study emphasized the actions taken by the Municipal Government of Guarujá (PMG) in 2022 as a tool for resolving socio-environmental conflicts without resorting to legal proceedings. The research focused on the specific case of the execution of macrodrainage works in the Santo Antônio neighborhood, which involved the relocation of 29 families from their homes, with equivalent compensation guided by a Terms of Conduct Adjustment (TCA). The qualitative research was based on documentary analysis, a systematic literature review, and interviews with the parties involved in the case. The study aimed to analyze how mediation techniques can contribute to resolving socio-environmental conflicts between public infrastructure projects and the local population. The research findings indicated that the initiatives of the PMG were essential in creating a mediation space, in which—through dialogue—the employees involved in the relocation process sought to address the families' demands, including amending clauses outlined in the Comparative Market Data Method for Urban Areas, adopted for compensation payments, provided that legal instruments were observed. This initiative made the population feel more secure in agreeing to the settlement; in other words, the interests of the majority of those involved in the conflict were satisfactorily met, leading the 29 families to accept the negotiation terms, With equivalent compensation through indemnities, guided by a Conduct Adjustment Term (TAC), this qualitative research employed documentary analysis, literature review, and interviews to investigate how mediation techniques influence the resolution of socio-environmental conflicts in public infrastructure projects with the local community. The research findings indicated that: 1 - The documentary analysis provided by the Municipal Government of Guarujá (PMG) revealed the initiation of administrative processes to individually address cases of compensated families, promoting transparency, efficiency, and legality in procedures, considering the use of public resources. 2 - To carry out the removal action with compensation, resources were allocated to hire specialized companies for property evaluation and social work, contributing to a more efficient approach in the execution of removal. 3 - Social work played a fundamental role in conflict resolution, establishing direct and frequent communication with affected families, resulting in an effective strategy to mitigate the negative impacts of removal actions. 4 - Regarding compensations, it became evident that reports were prepared by a specialized company, and evaluations were duly recorded by qualified professionals. Values were calculated considering criteria such as improvements made, age, and built area of the property, aligned with legal provisions. 5 - The PMG used various means of notification, including the Official Gazette, WhatsApp, and personal approaches in the intervention area for macro-drainage works. This approach reinforces the importance of the principle of publicity in public administration, ensuring transparency in actions and promoting citizenship. It is relevant to highlight that the creation of a negotiation space through dialogue between the PMG and affected residents was imperative for conflict resolution without resorting to judicialization, demonstrating an effective approach in process management.